Ward and Peppard Method Approach for Strategic Planning Information Systems XYZ Training Center - Quratul Ain; Norlaila Norlaila; Silvi Agustanti Bambang; Sukoco Sukoco; Dhani Ariatmanto; Adrianto M. Wijaya (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
ELTIBIZ Training Center is one of the training institutions engaged in non-formal education that has used information systems and information technology to make organizational performance more effective, efficient and increase competitiveness. The IS/IT strategy is needed to facilitate the management of information by the organization in winning the competition with competitors. In this study, IS/IT strategic planning uses the Ward and Peppard method starting from the process of analyzing the condition of the external and internal business environment, as well as the external and internal IS/IT environment. The analysis process uses SWOT analysis techniques, Value Chain analysis, Porter's Five Forces analysis, technology trend analysis and Mcfarlan's Strategic Grid matrix. The IS/IT strategic plan produced in this study includes an IS strategy in the form of a portofolio of future applications that can support business processes, an IS/IT management strategy in the form of a proposed system application development. The IS/IT strategic plan is written into an information system development roadmap as an implementation reference for the ELTIBIZ Training Center in the future whose implementation plan will be carried out within the next 5 (five) years. Keyword : Strategic Plan, Information System, Ward and Peppard, SWOT, Value Chain.